2021
DOI: 10.1007/s40264-021-01042-6
|View full text |Cite
|
Sign up to set email alerts
|

Public Perspectives of Using Social Media Data to Improve Adverse Drug Reaction Reporting: A Mixed-Methods Study

Abstract: Introduction Information on suspected adverse drug reactions (ADRs) voluntarily submitted by patients can be a valuable source of information for improving drug safety; however, public awareness of reporting mechanisms remains low. Whilst methods to automatically detect ADR mentions from social media posts using text mining techniques have been proposed to improve reporting rates, it is unclear how acceptable these would be to social media users. Objective The objective of this study was to explore public opin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…The included research showed that various social media outlets could raise the degree of women's health promotion [ 25 ], awareness of menstrual hygiene, understanding of breast cancer awareness [ 26 ], breastfeeding techniques [ 27 ], and adherence, self-perception and promotion of oral health [ 28 , 29 ], significant use of antibiotics [ 30 ], consistency with exercise, sexual health promotion [ 31 ], road safety awareness [ 32 ], smoking cessation, adverse drug reaction reporting [ 33 ], and many more in a row.…”
Section: Reviewmentioning
confidence: 99%
“…The included research showed that various social media outlets could raise the degree of women's health promotion [ 25 ], awareness of menstrual hygiene, understanding of breast cancer awareness [ 26 ], breastfeeding techniques [ 27 ], and adherence, self-perception and promotion of oral health [ 28 , 29 ], significant use of antibiotics [ 30 ], consistency with exercise, sexual health promotion [ 31 ], road safety awareness [ 32 ], smoking cessation, adverse drug reaction reporting [ 33 ], and many more in a row.…”
Section: Reviewmentioning
confidence: 99%
“…The current tools for text mining are imperfect, and many challenges remain for such approaches as identified by the Innovative Medicines Initiative (IMI) WEB‐RADR (Recognising Adverse Drug Reactions) project where a need for coordination to facilitate development, adoption and acceptance of such technology was clearly identified (Vivekanantham et al, 2020 ). Social media networks for health already exist, such as Health Unlocked, 7 but their use needs to be undertaken in a sensitive manner as studies have already shown that consumer trust is greater in activities undertaken for research or by regulatory authorities (Bulcock et al, 2021 ). In addition, some initial activities have been piloted as a reporting system.…”
Section: Assessmentmentioning
confidence: 99%
“…Third, future work into the sample bias of patient forums for other patient populations is necessary, as this study was limited to a single population in a single country. Nonetheless, our work is a stepping stone toward dissuading the concerns that researchers have expressed regarding the sample bias of social media [6,[16][17][18][19][20][21][22] by unraveling on which characteristics users differ significantly from the overall patient population. Future work could also investigate how compensatory measures can be implemented to statistically correct for sample bias.…”
Section: Future Work and Recommendationsmentioning
confidence: 99%
“…In fact, social media would be able to provide a more patient-centric view of which ADRs are most salient to patients on a day-to-day basis [15]. However, researchers as well as patients have expressed concern about sample bias on social media [6,[16][17][18][19][20][21][22]. Previous research on social media use in general shows that young people, women, and people of a higher socioeconomic class are generally highly represented [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%